1460 Sick leave benefits by diabetes mellitus: a retrospective epidemiological study. (24th April 2018) - Vitor, DVS; Batalini, VR; Brito, RV; Baptista, CA; Scardovelli, PI; Ferreira, LR
Abstract : Introduction: Diabetes mellitus is a disease that has a high prevalence around the world. In 2014, the World Health Organisation estimated that 422 million adults had the disease, worldwide. It is classified as being a chronic non-transmissible disease, and it is one of the main causes of disability, which can negatively affect productivity in active workers. In Brazil, the National Institute of Social Security (INSS) is responsible for granting benefits and salaries in cases of absenteeism due to illness. Methods: A retrospective study based on analysis of 184 patients who requested sick leave benefits due to diabetes mellitus from the Brazilian National of Social Security Institute (INSS), characterising the age, gender and employment situation through the ICD-10 (E10, E11 and E14) from January 2014 to February 2016. Results: The results showed that diabetes mellitus represented 34.2% of all sick leave requests associated with endocrine diseases (n=538). Considering just the diabetes ICDs, Insulin-dependent diabetes mellitus (E10) represented 63.6%, followed by non-insulin-dependent Diabetes (E11) with 24.4% and unspecified diabetes mellitus (E14) with 12%. The majority of beneficiaries were male (71.7%), associated with urban jobs (46.7%) especially administrative posts, ranging from 50 to 64 years old (63%). Discussion: The profile of workers who have requested benefits due to diabetes mellitus showed that the majority of beneficiaries were male adults, working in urban jobs ranging from 50–64 years old, mainly affected by Insulin-dependent diabetes mellitus disease. In addition, these beneficiaries can be more susceptible to workplace thermal conditions, stress and other issues inherent to the disease, such as hypo or hyperglycemia. These data should help in the implementation of strategies and measures to prevent the work disability caused by diabetes involving Brazilian workers and improve the worker's quality of life.